The Relationship Between Credit Accessibility, Financial Literacy, Loan Payment Behavior, and MSME Business Performance in Indonesia - Rudin, Rudin; Baresi, Irfan Sepria (Westscience Press, 2025)
This study examines the relationship between Credit Accessibility, Financial Literacy, Loan Payment Behavior, and Business Performance in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, employing Structural Equation Modeling (SEM-PLS) for data analysis. A sample of 170 MSME owners was surveyed using a Likert scale (1-5). The results reveal significant positive relationships between Credit Accessibility and Financial Literacy, Loan Payment Behavior, and Business Performance. Financial literacy and loan payment behavior also showed positive influences on business performance. The study highlights the importance of improving credit accessibility and financial literacy to enhance MSME performance in Indonesia. These findings offer valuable insights for policymakers, financial institutions, and MSME owners, suggesting that improving access to credit and fostering financial literacy can positively impact MSME growth and sustainability.